2009
DOI: 10.1093/humrep/dep125
|View full text |Cite
|
Sign up to set email alerts
|

Children born after cryopreservation of embryos or oocytes: a systematic review of outcome data

Abstract: Data concerning infant outcome after slow freezing of embryos was reassuring. Properly controlled follow-up studies of neonatal outcome are needed after slow freezing of blastocysts and after vitrification of early cleavage stage embryos, blastocysts and oocytes. In addition, child long-term follow-up studies for all cryopreservation techniques are essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
133
0
12

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(155 citation statements)
references
References 88 publications
10
133
0
12
Order By: Relevance
“…In fresh donor cycles, recipients have hormone levels more comparable to those in a natural conception cycle, which may in part explain the improved rates of implantation, clinical pregnancy, and live births [38], as well as lower rates of LBW, SGA [8], and preterm birth [5]. Results of clinical studies and meta-analyses of IVF pregnancies indicate the risks for SGA, preterm birth, LBW, antepartum hemorrhage, and perinatal mortality are significantly reduced with frozen compared to those with fresh embryo transfers [2,[39][40][41][42]. The risk of prenatal bleeding, placental complications, and postpartum hemorrhage has been shown to be higher in both subfertile and IVF pregnancies compared to those conceived spontaneously [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…In fresh donor cycles, recipients have hormone levels more comparable to those in a natural conception cycle, which may in part explain the improved rates of implantation, clinical pregnancy, and live births [38], as well as lower rates of LBW, SGA [8], and preterm birth [5]. Results of clinical studies and meta-analyses of IVF pregnancies indicate the risks for SGA, preterm birth, LBW, antepartum hemorrhage, and perinatal mortality are significantly reduced with frozen compared to those with fresh embryo transfers [2,[39][40][41][42]. The risk of prenatal bleeding, placental complications, and postpartum hemorrhage has been shown to be higher in both subfertile and IVF pregnancies compared to those conceived spontaneously [43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…The low birthweight rate among singletons was 18 % and among multiple 80 %. The premature delivery rate was 26 % for singletons and 71 % for multiple pregnancies [43]. However, long-term child follow-up studies are lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that singletons born after FET have a perinatal outcome more comparable to those born after natural conception than to those born after fresh embryo transfer (fresh ET), having higher birth weight and less pregnancy complications [2][3][4][5][6][7][8][9][10]. However, higher risk for birth of a singleton being large for gestational age (LGA) has been revealed after FET [2,3,7,8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%